2017
DOI: 10.1080/13813455.2017.1419366
|View full text |Cite
|
Sign up to set email alerts
|

The downregulation of sweet taste receptor signaling in enteroendocrine L-cells mediates 3-deoxyglucosone-induced attenuation of high glucose-stimulated GLP-1 secretion

Abstract: 3DG attenuates high glucose-stimulated GLP-1 secretion by reducing STR subunit expression and downstream signaling components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…If so, competitive inhibition between 3DG and high glucose may emerge. Interestingly, we previously reported that acute exposure to 3DG reduces GLP-1 secretion by downregulating the STR expression under high-glucose conditions [21]. The above results could be explained by the idea that 3DG treatment may partially occupy STR substrate binding sites under high-glucose conditions and high concentrations of glucose may be more potent and more effective than 3DG.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…If so, competitive inhibition between 3DG and high glucose may emerge. Interestingly, we previously reported that acute exposure to 3DG reduces GLP-1 secretion by downregulating the STR expression under high-glucose conditions [21]. The above results could be explained by the idea that 3DG treatment may partially occupy STR substrate binding sites under high-glucose conditions and high concentrations of glucose may be more potent and more effective than 3DG.…”
Section: Discussionmentioning
confidence: 92%
“…Previously, we have reported that an acute administration of 3DG leads to a decrease in glucose-stimulated GLP-1 secretion in vivo [17] and in vitro [21]. In this study, we examined the effect of an acute administration of 3DG on basal GLP-1 secretion in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several parameters have been proposed to affect the secretion and concentration of GLP-1 including glucose [19], fat [19], bile acids [20], inflammatory markers [21, 22], 3-deoxyglucosone [23] (generated from carbohydrates) and the presence of obesity [24] and type 2 diabetes [18].…”
Section: Discussionmentioning
confidence: 99%
“…A smaller study in twins showed that in monozygotic pairs discordant for BMI and liver fat the GLP-1 secretion was reduced at 60 min during an OGTT [45]. Furthermore, an experimental study by Wang et al has shown interesting results where 3-deoxyglucosone (3DG), a precursor for advanced glycation end-products known to be able to induce glucose intolerance, reduces GLP-1 release [46]. Against this background of GLP-1 level alterations our study finding with elevated GLP-1 levels in subjects with a recent ischemic stroke add information.…”
Section: Strengths and Weaknesses In Relation To Other Studiesmentioning
confidence: 99%